Optimalisasi Pemanfaatan Aset Lahan Pertanian Organisasi Muhammadiyah Cabang Rappang - Reza Asra; Muhammad Bibin; Aksal Mursalat; M Irwan (Fakultas Pertanian, Universitas Timor, 2022)
Muhammadiyah Association has attempted to collect data on land assets owned and controlled with the aim of managing and using land assets effectively, which is oriented towards the development of the welfare of the people. This study aims to determine the distribution of land assets with a Geographic Information System (GIS) approach and to analyze the optimal form of utilization of land assets of the Muhammadiyah Regional Board (PDM) Rappang Branch. This research begins by making a reference map to identify the distribution of land assets using the Visual On-Screen Digitizing method. Next is the hierarchical analysis process (AHP) to determine alternative forms of optimal land use. The total land assets owned by PDM Rappang Branch are 171,931.39 m2. Most of the land assets owned are in Rijang Panua village at 67.85%. The alternative priority offered in optimizing land assets of the Rappang branch of PDM is agricultural activities (34.98%). The second alternative is to cooperate with other parties (33.81%). The third alternative is to build a green area (17.68%), and the last alternative is to build public facilities (13.52%).